Serahsi'nin Mebsut adlı eserinin siyer bölümünün tahkik ve tahlili - Abedalqader, Malek (My University, 2021)
Çalışmamızın konusu, Hanefi fıkhının temel kaynaklarından biri olan Serahsi'nin Mebsut adlı eserinin “Kitabü’s-Siyer kısmının tahkiki ve tahlilidir. Günümüzde uluslar/ devletler arası hukuk alanına giren meselelere değinen “Siyer” bölümü Müslümanların oldukça erken bir dönemde hukuk ilmine yaptıkları katkıları göstermektedir. Bu bölümde büyük ölçüde müslümanlarla gayrimüslimler arasındaki ilişkileri konu edinmektedir. Bu bölümde müşrik, zimmi, mürted ve isyancılarla ilişkiler, bu gruplarla ilgili savaş, barış, ticari muameleler, evlilik, yargılama ve benzeri alanlardaki hükümler ele alınmaktadır. Bu konular Hanefi mezhebine göre detaylı biçimde açıklanıp bazen diğer mezheplerle, özellikle Şafii mezhebiyle karşılaştırılmaktadır. Günümüzde de bu konular önemini korumaktadır. Dünyanın küçük bir köy haline gelmesi, Müslümanların gayrimüslim ülkelere göç etmeleri, konuyla ilgili birçok kavramın yanlış anlaşılması bu alanda çalışma yapmamızın nedenleri arasındadır. Bu konularda ve genel anlamda fıkıhta Hanefi mezhebinin öncü ve erken döneme ait ictihadlarının ele alındığı Serahsi’nin Mebsut’una, önemine rağmen tahkik ve inceleme yönünden gereken hakkı verilmemiştir. Birçok kez basıldığı ve tahkik edildiği iddia edilmesine rağmen ne yazık ki bu baskıların hiç biri günümüz ilim çevrelerinde genel kabul gören tahkik kurallarına uymamakta ve birçok hata içermektedir. Mebsut’un devasa hacmine kıyasla çalışmamızın alçakgönüllü ve küçük boyutuna rağmen, bu çalışmada öne koyduğumuz hedefe ulaşmak için çaba gösterdik. Bu çalışmada ilmi ölçüler içinde tahkik kurallarına uymaya garet ettik. Ayrıca eserde yer alan bazı meseleleri günümüz devletler arası hukukuyla mukayese ettik. Mebsut’un tamamının tahkik ve tahlil edilmesi yönünde bir katkı ve ilk adım olmasını arzu ettiğimiz çalışmamızın bu alanda yapılacak çalışmalara öncülük etmesini ve bu eser ve alan üzerine nicelik ve nitelik açısından daha zengin çalışmaların yapılmasını ümit etmekteyiz.

The subject of this thesis is the study and investigation of the “Al-Siyar” book from (Al-Mabsout) book by Imam Al-Sarakhsi. which is one of the classical Arabic Islamic manuscripts and one of the famous and important books. Additionally, it is considered as the first authentic references, and one of the largest books of Hanafi comparative jurisprudence. SIYAR is a book that address the rulings and issues related to dealing with non-Muslims holding different names and attitudes towards Islam and Muslims. The book includes several important topics as the following: the treatment of Muslims with the warlike people of the polytheists and others, the people of the Covenant from the trustees and the people of the dhimma, and with the apostates, and with the rebels , discussing issues related to the commercials treatment of the people of war, and what is related to conduct the peace with them, the provisions of marriage among them, jihad and dawa, the Islamic army’s treatment, what is related to booty, and other chapters that include various provisions.lastly, issues and details in this broad chapter. All of this is according to what is adopted in the Hanafi madhhab, sometimes compared with other madhhabs, especially the Shafi’i madhhab, with an explanation and detail by Imam al-Sarakhsi. We chose this topic due to of its importance and sensitivity specially in these days. As the events and changes that we are witnessing from global international openness in all fields in the worlds. Also, the migrations of Muslims to non-Muslim countries in an unprecedented way, and the imbalance of many concepts around it, rather the spread of concepts that are not related to Islam among Muslims themselves before others. And in fact, we were encouraged to choose this topic due to the strength and depth of the opinions of the Hanafi madhhab, especially in this chapter. Despite the importance of this huge reference, still it did not give the value that should be given to a treasure like it. Al-Mabsout was achieved several times, ancient and modern, or we say that it was achieved once in the past and then reprinted after it many times. However, all the versions unfortunately didn’t elaborate or followed investigations’ rules and foundations. Accurate Scientific, did not rise to a level commensurate with the value of this great book. Although the thesis that we work is small in comparison to the Al-Mabsout book’s and the other large elaborative investigation works, but we will strive to achieve the most important goal in any work, which is the elaboration and accuracy according to the rules and standards. And that our effort is to contribute and motivate to achieve and study the book Completely fine-tuned with the foundations and standards of the art of investigation. As a result, extracting it in a new and appropriate form, feeding the Islamic jurisprudence library with it, to include it with other jurisprudential literature for study, research, and benefit from it more and more in the future, Inshallah.
Keywords: Al-Hakim ash-Shahid; Al-Kafi; Al-Mabsout; Al-Sarakhsi; As-Siyar; EL-KÂFÎ; EL-MEBSÛT; ES-SERAHSÎ; ES-SEYER; HÂKİM EŞ ŞEHÎD; HANEFİ MEZHEBİ; International Relations; Islam; İslam; The Hanafi School; ULUSLARARASI İLİŞKİLER